PENCEGAHAN STRESS AKIBAT TINDAKAN BODY SHAMMING DAN BULLYING DENGAN TEKNIK AFIRMASI POSITIF PADA SISWA DI SMK YP 17 PARE - Melani Kartika Sari; Moch Maftuchul Huda; Mufadilah Isnatul (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
Adolescence is a developmental period of transition from childhood to adulthood. Adolescence is marked by changes in the period of growth and development that occur very rapidly, both physically, psychologically, and intellectually. The impact that occurs is that it will hamper the development of behavior and psychosocial skills so that it shows pathological behavior that is not good, such as bullying and body shamming, which cause stress in adolescents. This is due to the lack of student information about stress prevention. The purpose of this community service is to know that there is an increase in the insight of cadres and their members in preventing stress. The method used is the positive affirmation technique. The population is 48 students, a sample of 33 students consists of 5 student PMR cadres and 28 student members. PMR cadres of selected students from PMR Wira who will be empowered The sample is expected to be able to continue the positive affirmation technique throughout the PMR population. The community service instrument uses a questionnaire sheet. The results of the cadres before the intervention were all (100%) in the good category with a mean of 85 (good), after the intervention, all (100%) were in the very good category with a mean of 100 (very good). The results of the PMR members before the intervention were all (100%) in the poor category with a mean of 29.01, after the intervention, almost all (96.4%) were in the good category with a mean of 84.82 (good). This means that cadres and PMR members experienced an increase in the insight score on stress prevention. The results of the analysis showed that there was an increase in scores before and after the intervention for PMR cadres and members. The positive affirmation method is packaged in power points and demonstrations so that it is more interactive, interesting, effective, and insightful for respondents. It is better if the knowledge of stress prevention can be disseminated to all school members in an effort to prevent stress due to bullying and body shamming.